Behavioral Biases and Regional Diversity: An In-Depth Analysis of Their Influence on Investment Decisions - A SEM & MICOM Approach - Muzzamil Rehman; Babli Dhiman; Ngoc-Diep Nguyen; Rajesh Dogra; Anjali Sharma (Qubahan Academic Journal)
The Basic purpose of the study was to understand the impact of behavioral biases on Global Investors investment Decisions and whether there is any significant difference of the impact on investment Decisions of Global investors due to regional diversity. The data was collected from 467 Global investors from China and India SEM was used to test the hypothesis and Followed by Multi- group analysis. The results revealed that Behavioral biases have a significant on investment decisions of Global Investors. The impact was found more on India Global investors than that of China. The insight into how regional diversity can magnify or attenuate these biases offers valuable guidance for global investment firms seeking to tailor their services to a culturally diverse clientele. Understanding the interplay between behavioral biases and regional disparities allows for the development of region-specific financial products and advice, better aligning investment strategies with the unique needs and risk tolerance of investors from different parts of the world. The originality of this research lies in its nuanced examination of how behavioral biases, in conjunction with regional disparities, can offer valuable insights for both investors and financial practitioners, enhancing our comprehension of the intricate dynamics at play in the global investment sphere.